ECONOMIC EXPLORATION, GEOECOLOGICAL RESOURCES AND THEIR RELATIONS WITH THE ANTHROPOCENE (ADMPG Journal, 2023)
In this work, the economic exploitation of nature through the transformation and use of geoecological resources such as consumer goods and services, materialized by the notion of economic development, is the basis of reflection around the Anthropocene, where fauna, flora, soils and rocks are converted into inputs , catalogued, priced and marketed. Thus, the article aims to reflect on the economic exploitation of geoecological resources through the logic of economic development and its relationship with the acceleration of the Anthropocene. It takes as reference authors such as Rist (2002) and Bellingieri (2017), foundations on geoecological resources in Alves (2007) and Gorayeb (2014) and the Anthropocene in works such as those by Steffen et. al. (2011; 2016) and Haraway (2016). It is a field and documentary research, carried out between June and July 2021, having as unit of analysis three geosites of the Araripe Geopark in the Cariri region of Ceará. The research indicated anthropic interference in geosites, with environmental and geological consequences. The contribution of this study lies in the relationship between the notion of development and the use and transformation of geoecological resources as a concept and object of the exact sciences, around the discussion of the Anthropocene acceleration as a phenomenon of interest to all sciences.